Creating Agricultural Markets : How the Ethiopia Commodity Exchange Connects Farmers and Buyers through Partnership and Technology - Haile, Abenet Bekele (International Finance Corporation, Washington, DC, 2018)
Commodity exchanges can provide emerging market economies with orderly, transparent, and efficient markets by acting as mechanisms that mitigate price risk, discover equilibrium prices, and connect buyers and sellers. Exchanges can also reduce transaction costs and information asymmetries by using technology to disseminate market information while creating better supply chains. The Ethiopia commodity exchange is striving to transform Ethiopia’s agriculture sector from a fragmented one marked by high transaction costs and low quality standards to a thriving and reliable part of the country’s economy. Ethiopia’s exchange continues to expand its activity across the farming regions of the country.